Effective and new potent drug combination: Histone deacetylase and Wnt/β‐catenin pathway inhibitors in lung carcinoma cells. Issue 9 (29th April 2019) - Akgun, Oguzhan; Erkisa, Merve; Ari, Ferda
Abstract: Lung cancer is the most commonly diagnosed cancer worldwide with a high mortality rate. In this study, the therapeutic effect of combination valproic acid and niclosamide was investigated on human lung cancer cell line. The effects of the compounds alone and combination therapy on cell viability were determined by sulforhodamine B and adenosine 5′‐triphosphate viability assays. Flow cytometry was used to determine the cell death mechanism and DNA damage levels responsible for the cytotoxic effects of combination therapy. The presence of apoptosis in cells was supported by fluorescence microscopy and also by using inhibitors of the apoptotic signaling pathway. The increase in cellular reactive oxygen species (ROS) level in combination therapy was determined by H2DCFDA staining. The effect of N‐acetyl‐l ‐cysteine combination on ROS increase was investigated on cell viability. In addition, the expression levels of the proteins associated with epigenetic regulation and cell death were analyzed by Western blotting and gene expression levels were determined using real‐time quantitative polymerase chain reaction.It was observed that the combination therapy showed a cytotoxic effect on the A549 lung cancer cells compared to the individual use of the inhibitors. The absence of this effect on normal lung cells revealed the presence of a selective toxic effect. When the mechanism of cytotoxicity is examined, it has been observed that combination therapy initiates the activation of tumor necrosis receptors and causes apoptosis by activated caspase. It was also observed that this extrinsic apoptotic pathway was activated on the mitochondrial pathway. In addition, ER stress and mitochondrial membrane potential loss associated with increased ROS levels induce cell death. When the data in this study were evaluated, combination therapy caused a dramatic decrease in cell viability by inducing the extrinsic apoptotic pathway in lung cancer cell line. Therefore, it was concluded that it can be used as an effective and new treatment option for lung cancer. Abstract : In this study, the therapeutic effect of combination the histone deacetylase inhibitor valproic acid and the Wnt/β‐catenin survival pathway inhibitor niclosamide were investigated on human lung cancer cell line. Our results show that combination therapy of valproic acid and niclosamide caused a dramatic decrease in cell viability by inducing the extrinsic apoptotic pathway in lung cancer cell line. Our results can be used as an effective and new treatment option for lung cancer.